An Emotion Regulation and Impulse Control (ERIC) Intervention for Vulnerable Young People: A Multi-Sectoral Pilot Study - Hall, Kate; Youssef, George; Simpson, Angela; Sloan, Elise; Graeme, Liam; Perry, Natasha; Moulding, Richard; Baker, Amanda L.; Beck, Alison K.; Staiger, Petra K. (Frontiers in Psychology, 2021)
Objective: There is a demonstrated link between the mental health and substance use comorbidities experienced by young adults, however the vast majority of psychological interventions are disorder specific. Novel psychological approaches that adequately acknowledge the psychosocial complexity and transdiagnostic needs of vulnerable young people are urgently needed. A modular skills-based program for emotion regulation and impulse control (ERIC) addresses this gap. The current one armed open trial was designed to evaluate the impact that 12 weeks exposure to ERIC alongside usual care had on young people’s ability to regulate emotions, as well as examine potential moderating mechanisms. Methods: Seventy nine young people (50.6% male; M=19.30; SD=2.94) were enrolled to the 12 week intervention period. Twenty one practitioners from youth and community health services delivered relevant ERIC modules adjunct to usual care. Linear mixed effects regression (with random intercept) was used to examine change over time across the primary outcome of emotion dysregulation and secondary outcomes of depression, anxiety, stress, experiential avoidance and mindfulness. Moderation analyses were conducted to test whether the magnitude of change in emotion dysregulation moderated change over time in secondary outcomes. Results: Analyses revealed significant improvement in the primary outcome of emotion dysregulation with a moderate effect size (Mean Change= -10.24, 95% CI(-14.41, -6.06; Cohen’s dav = -0.53), in addition to decreases in the secondary outcomes of depression, anxiety, stress and experiential avoidance. No improvements in mindfulness were reported. Moderation analyses revealed that the residualised change over time in emotion dysregulation moderated the change over time in symptoms of distress, depression, anxiety, stress, experiential avoidance, and mindfulness. Conclusion: Reductions in the severity of emotion dysregulation, depression, anxiety, stress and experiential avoidance are promising, and were evident despite the complexity of the participants and the diversity of the service setting. The improvements found in each outcome were only observed for those young people whose emotion regulation also improved, providing preliminary evidence for the role of emotion regulation as a key treatment target in this population.